ARTIFICIAL INTELLIGENCE TECHNIQUES IN MULTIMEDIA (Multidisciplinary Journal of Science and Technology, 2024)
Artificial Intelligence (AI) has emerged as a transformative force in the field of multimedia, revolutionizing content creation, analysis, and delivery across various industries. This paper explores the integration of AI techniques in multimedia applications and its profound implications for enhancing creativity and efficiency. Drawing upon existing literature and case studies, the paper examines the impact of AI-powered multimedia technologies on industries such as entertainment, advertising, education, and healthcare. Furthermore, the paper identifies key challenges and opportunities associated with the integration of AI and multimedia, including technical limitations, ethical considerations, and societal implications.